Microbiome analyses of the Uraim River in the Amazon and georeferencing analyses to establish correlation with anthropogenic impacts of land use - Cardenas-Alegria, Oscar Victor; Ferreira, Victor Benedito Costa; Noguera, Wylerson Guimarães; Martins, David Tavares; Martins Neto, Artur Pedro; Monteiro Pontes, Paulo Rógenes; Lopes Cavalcante, Rosane Barbosa; Aguiar Alves, Sandy Ingrid; Luiz da Costa da Silva, Artur; Gomes Costa, Rosilene; Franco de Los Santos, Edian Franklin; Azevedo, Vasco Ariston de Carvalho; et al. (Frontiers in Environmental Science, 2024)
One of the primary challenges in the spread of infectious diseases is the consumption of poorly or untreated water, which is increasingly being used due to the growth of different human activities and the effect of urbanization on freshwater sources, which are often used for consumption purposes. The determination of pathogenic bacteria in freshwater rivers influenced by anthropogenic activities allows for the assessment of the impact these factors have on water quality. Thus, the purpose of this study was to identify the diversity of pathogenic bacteria and virulence genes in the Uraim River in the northern region of Brazil. For this purpose, surface water was collected from five points with varying degrees of anthropogenic impact along the Uraim River. In situ measurements of physicochemical components were conducted, and metagenomic analysis was used for the identification of pathogenic bacteria and virulence genes. Regarding the physicochemical parameters, variability was observed among the different analysis points, as well as diversity among bacteria and virulence genes. Notably, enterobacteria and the ESKAPE group were highlighted among the bacteria, with significant negative associations found between dissolved oxygen and the diversity of virulence genes and between deforestation and population density with the presence of ESKAPE group bacteria.